PENYELENGGARAAN PELAYANAN PUBLIK DI KANTOR KECAMATAN TARAKAN TENGAH DALAM PERSPEKTIF GOOD GOVERNANCE - Icwan Rohadi (Universitas Borneo Tarakan, 2026)
This article examines the implementation of public services at the Tarakan Tengah District Office from the perspective of good governance. The main issues are the authority of public service administration and the implementation of public services based on the principles of good governance. This study uses normative legal research with statutory and conceptual approaches. The results show that the district office has a strategic position as a territorial apparatus closest to the community, especially in coordinating government administration, public service, and community empowerment. The authority and mechanism of administrative services must be implemented based on legality, professionalism, transparency, accountability, responsiveness, legal certainty, and equality of service. Public service standards, complaint handling, access to information, supervision, and fair treatment are essential elements to ensure that services at the district level are not merely administrative procedures, but also instruments for realizing clean, responsive, and welfare-oriented local governance.